THE LANGUAGE OF YOUNG MACEDONIAN AND TURKISH SPEAKER ON SOCIAL NETWORKS - Trifunovska Janik, Sunchica (International Scientific Journal Vision, 2024)
The subject of this paper is the language used by the young generations in our country, both native speakers of Macedonian and native speakers of Turkish, in their communication on social networks. For the purposes of this paper, several young people of different ages were surveyed, in order to better perceive the differences and similarities in their mutual communication. Nowadays, all people, regardless of age, are in some way dependent on social networks, where the use of literary language among young people, unfortunately, is reduced to a minimum. During daily communication on the Internet, we insert new words and abbreviations mostly from the English language without being aware of it and without finding a suitable replacement in our language. This is exactly why we should be careful how we speak and write in our native language, because that’s the only way we’ll manage to save it from the daily influences we face, above all from the influence of social networks.